Analysis and optimization of epicyclic mechanisms with mutually meshed satellites for engineering and industrial applications - Bozherikov, Sylvester; Uzunov, Hristo; Dechkova, Silvia; Tsoneva, Mina (Zielona Góra: Uniwersytet Zielonogórski)
This study presents an in-depth kinematic and dynamic analysis of an epicyclic gear mechanism with mutually engaged satellites, aiming to optimize its characteristics and overall efficiency. The primary objective is to analyze its operational performance and propose optimization solutions to enhance its effectiveness. The research focuses on the complex interactions between the satellites, which ensure even load distribution, reduce localized stresses, and increase load capacity.
Keywords: epicyclic gear mechanism; torque; satellites; involute profile; CAD systems